(001)-exposed TiO2 microcrystals decorated with few-layer nanobelts for enhanced photocatalytic activity. (January 2019) - Xing, Huan; Wen, Wei; Wu, Jin-Ming
Graphical abstract: Surface decorations of (001)-facet exposed TiO2 microcrystals improve significantly the photocatalytic activity towards phenol degradations under UV light illumination. Highlights: Few-layer TiO2 nanobelts were precipitated on TiO2 microcrystals via a solution approach. Both nanobelts and microcrystals were anatase TiO2 . The belt-on-core hierarchical structure possessed enhanced photocatalytic performance. A synergistic effect between TiO2 microcrystals and nanobelts is anticipated. Abstract: TiO2 microcrystals exposing 001 facets are of potential applications in photocatalysis; however, the photocatalytic activity is limited by micrometer sizes. Herein, we report a compositing tactic to compensate the photocatalytic activity through surface decorations with few-layer TiO2 nanobelts. Hydrothermally synthesized anatase TiO2 microcrystals exposing (001) facets were immersed in a precursor solution at 60 °C, on which hydrogen titanate nanobelts precipitated vertically on the surface. A subsequent calcination in air at 400 °C was followed to decompose titanate nanobelts to anatase TiO2 with the nanostructure maintained. The coverage of TiO2 nanobelts can be controlled by varying the immersing duration. When utilized to assist photodegradation of phenol in water under UV light illumination, the composited TiO2 exhibited a reaction rate constant 2.3 times that of the pristine TiO2 microcrystals. A synergetic effect arising from the microcrystals and surface decorated nanobelts is believed to contribute to the enhanced photocatalytic activity.